PHYTOCHEMICAL ANALYSIS AND SUPPRESSION OF INFLAMMATORY TARGETS BY ADATHODA VASICA - Reddy, Amala; Sundaresan, Sujatha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: A persistent and chronic inflammation may act as an underlying definition for many of the long-term illness such as diabetic foot ulcer, Alzheimer's disease and rheumatoid arthritis. Folklore medicinal plants provide immense health benefits with new remedies. Active compounds from plants containing alkaloids and phenolic compounds (flavonoids and tannins) possess antioxidant and anti-inflammatory activity. The leaves of Adhatoda vasica are most known for its effectiveness in treating respiratory diseases such as asthma, chronic bronchitis, and other respiratory conditions. In this report, we investigated the possible action of A. vasica against inflammation. Methods: Solvents with varying polarity (Hexane, dichloromethane, ethyl acetate, and methanol) were used for the sequential extraction of leaves of A. vasica Linn (Family: Acanthaceae). The antiâ€inflammatory activity was assessed using simple in vitro methods. Phenols, flavonoids, phytosterols, saponins, alkaloids, and tannins were analyzed qualitatively using standard protocols. Antiâ€inflammatory activity was evaluated using albumin denaturation assay, membrane stabilization assay and proteinase inhibitory activity. Aspirin (diclofenac) was used as a standard drug for the study of anti-inflammatory activity. Results: Our results substantiated that methanolic extract of A. vasica gave a maximum yield of 12.5% and apparently all bioactive phytochemical constituents were at a higher concentration in the methanolic extract. Methanolic extract of A. vasica showed a significant inhibition of the heat-induced albumin denaturation, red blood cells membrane stabilization, and proteinase inhibitory effects with 86Â±1.46, 88Â±1.24, and 96Â±0.93% for 1000 Î¼g/ml, respectively. Conclusion: The above results delineate that the bioactive components were extracted using high polar solvent are mostly flavonoids and related polyphenols. These compounds may be the active constituents to render the anti-inflammatory activity to A. vasica.